2004
DOI: 10.1111/j.1751-0813.2004.tb12685.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a test and control program for bovine Johne's disease in Victorian dairy herds 1992 ‐ 2002

Abstract: The TCP caused a marked decline in the number of clinical cases, probably because animals in which clinical disease was imminent were detected by testing and removed. A reduction in prevalence of reactors occurred only when most herd members were born after the TCP started. The sensitivity of the ELISA appears to be low based on the large number of reactors that were negative at T1 but were positive at later tests. Low sensitivity of diagnostic tests and the long incubation period of the disease limits meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…The level of adoption observed here was larger than other studies (Wraight et al, 2000;Jubb and Galvin, 2004;Ridge et al, 2005;Sorge et al, 2010b). However, it is important to note that behavior in this study was defined as the uptake or adoption of at least one on-farm management practice specifically for JD control, and as such there is no opportunity to assess the retention and sustainability of the behaviors that were reported to have changed.…”
Section: Study Limitationsmentioning
confidence: 80%
See 1 more Smart Citation
“…The level of adoption observed here was larger than other studies (Wraight et al, 2000;Jubb and Galvin, 2004;Ridge et al, 2005;Sorge et al, 2010b). However, it is important to note that behavior in this study was defined as the uptake or adoption of at least one on-farm management practice specifically for JD control, and as such there is no opportunity to assess the retention and sustainability of the behaviors that were reported to have changed.…”
Section: Study Limitationsmentioning
confidence: 80%
“…Although RA-based JD control programs have been widely implemented, their efficacy is largely dependent on the veterinarian's ability to communicate with his or her clients and the producer's willingness to adopt the recommended on-farm management practices for JD control (Sorge et al, 2010b). Several studies examining the uptake of on-farm management practices to control JD have reported poor producer uptake (Wraight et al, 2000;Jubb and Galvin, 2004;Ridge et al, 2005;Sorge et al, 2010b). This is likely due to the inability of the RA, and the veterinarian administering the RA, to address the factors associated with behavioral change (Sorge et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic tests have low sensitivity, especially in the early stages of the disease. The within‐herd prevalence is typically low in cattle . Practically, this means that the majority of farmers do not know precisely how or when infection first entered their herd and this obscures the full economic impact of the disease.…”
Section: Bjd In Australiamentioning
confidence: 99%
“…Several studies have investigated the control of PTB in affected dairy farms [7-12], but only a few in beef farms [13,14]. Both test-and-cull strategies and strategies of management improvement have been used in such control programs.…”
Section: Introductionmentioning
confidence: 99%